Corky, a gypsy-like retrotransposon is differentially transcribed in Quercus suber tissues. - Rocheta, Margarida; Carvalho, Luísa; Viegas, Wanda; Morais-Cecílio, Leonor (BMC research notes, 2012)
Background: Transposable elements (TEs) make up a large part of eukaryotic genomes. Due to their repetitive nature and to the fact that they harbour regulatory signals, TEs can be responsible for chromosomal rearrangements, movement of gene sequences and evolution of gene regulation and function. Retrotransposon ubiquity raises the question about their function in genomes and most are transcriptionally inactive due to rearrangements that compromise their activity. However, the activity of TEs is currently considered to have been one of the major processes in genome evolution. Findings: We report on the characterization of a transcriptionally active gypsy-like retrotransposon (named Corky) from Quercus suber, in a comparative and quantitative study of expression levels in different tissues and distinct developmental stages through RT-qPCR. We observed Corky’s differential transcription levels in all the tissues analysed. Conclusions: These results document that Corky’s transcription levels are not constant. Nevertheless, they depend upon the developmental stage, the tissue analysed and the potential occurring events during an individuals’ life span. This modulation brought upon by different developmental and environmental influences suggests an involvement of Corky in stress response and during development.
Keywords: corky; expression; ltr retroelement; Quercus suber; rt-qpcr